An android application for : MYBAS / Fatin Ain Najwa Che Hashim - Che Hashim, Fatin Ain Najwa (2018)
MyBAS is a one of the public transports based on regular operation of transit buses along the route. The bus transportation has mainly widely used among the city people due to avoid traffic. The other reason why people are using the bus transportation is because of its cheap price to reach destination and it is affordable among all people. Nowadays, almost of the entire passenger have their own smart phone and ease their daily life with a variety application. Mobile application also known as mobile apps are developed for small handheld gadget and devices, such as mobile phones, smart phones, personal digital assistant (PDA), tablet and many more. This project is conducted to create a mobile app to serves the user as a medium to provide the information about myBAS in Perlis. It is an interactive medium to use by passenger. This app will help the user to discover the closest position of bus stop from user current location by using interactive map and also provide other useful information. Unlike the website, this app will remain in the pocket, so the user can continue to use anytime, anywhere by just install this application in Google Play Store. The aim of this study is to develop the mobile application to provide the information for user. It is also useful for visitor who rarely comes in Perlis and increase interest the visitor to come visit Perlis by using the development of this mobile application for them to go from one place to another places. The objective of this study is to develop a mobile application of myBAS in the android-based platform. Data that needed to be collecting were building coordinate for each bus stop, departure time and bus fare. In this research, the Android Studio software to create the mobile application was used and all information in Microsoft Excel. The expected outcome will show the application can be operated. This app consists of information about the closest position of bus stop from current location, the departure time, bus fare and also the route planner. This application also provides the hotline number for emergency cases.